THE BENEFITS OF USING NATURAL SWEETENERS IN SPECIAL NUTRITION. A MINI REVIEW - Mariana Violeta POPESCU; Adriana DABIJA; Ancuța CHETRARIU (Food and Environment Safety)
Currently, with the continuous improvement of living standards, people are paying more and more attention to nutrition and body's health. The daily caloric intake represented by sugar should not exceed 10%, and a reduction in this percentage decreases the risks of health problems, such as diabetes and cardiovascular disease. However, it is the sweet taste that we like and attracts us, so it is necessary to find alternatives to refined sugar. The safest and most effective natural sweeteners that can successfully replace sugar are: stevia, honey, and maple syrup. Stevia is the only natural non-caloric sweetener, has a sweetness 50 to 350 times higher than sugar, and can be used in any diet due to its caloric index of 0 value and its high carbohydrate content. It does not influence blood sugar levels, which indicates that stevia is the safest sweetener. Honey is another natural sweetener that can successfully replace sugar and, at the same time, provide health benefits. Due to the composition of honey, it has an antioxidant, hepatoprotective, cardioprotective, antibacterial, and anti-inflammatory effect, the fructose in honey helps lower blood sugar in diabetes patients, but it should be consumed in moderation. Another natural sweetener that can be used as a sugar substitute in the diabetic diet is maple syrup, with a high content of abscisic acid phytohormone with antidiabetic properties. Taking into account the requirements of consumers to lead a diet as healthy as possible, food industry has tried to find the best ways to adapt so researchers have shown a great interest in adapting the reformulation of foods, beverages and sweets by replacing sugar with natural sweeteners, which can have a low glycemic index, low calorie content but, most importantly, provides a wealth of nutrients.